Influence of Infiltration Methods on Runoff Estimation for Sustainable Rainwater Harvesting in Arid Regions - Ismail Abd‐Elaty; Alban Kuriqi; Elsayed M. Ramadan; Marmar Mabrouk; Ibrahim Elbagory (Irrigation and Drainage, 2026)
Arid regions face severe water stress due to limited rainfall and growing water demand, making accurate runoff estimation essential for sustainable water management. Infiltration processes strongly influence both hydrograph volume and peak discharge, and their accurate estimation is critical for hydrological modelling. This study applies the Watershed Modelling System (WMS) to evaluate rainwater harvesting potential in the Wadi El‐Aawag watershed, southwestern Sinai, Egypt, using four infiltration loss estimation methods: Uniform Loss (LU), Green–Ampt (LGA), Holtan (LH) and the Soil Conservation Service (SCS) curve number method. Each method accounts for soil type, land cover and infiltration characteristics, enabling assessment across recurrence intervals of 5, 10, 25, 50 and 100 years. The results indicate considerable variation in runoff response across the selected methods. The estimated runoff volumes were 35.11, 24.10, 31.65 and 23.57 million m 3 for LU, LGA, LH and SCS, respectively, for recurrence intervals of 100 years. Among the tested approaches, the SCS method provided the most reliable and realistic estimates for the study area. These findings emphasise the importance of method selection when modelling infiltration losses and highlight the role of robust hydrological assessment in optimising rainwater harvesting, mitigating drought risks and enhancing long‐term water security in arid regions.

Bridging food and clinical neurotherapeutics in ADHD management: A comprehensive comparative evidence on phytochemicals and non-pharmacologic paradigms - Eman Maher Zahran; Aliaa Gamal; Motaz M. Hassan; Mohamed M. Elsayed; Eyad Y. Elhamadany; Nursin Mustafa Bayoumi; Tarek Gamal Ebrahim; Fatma Alzahraa Mokhtar; Islam M. Abdel-Rahman; Hesham A. Abou-Zied; Usama Ramadan Abdelmohsen (Food Bioscience, 2026)

Impacts of spills on water quality and treatment plants: A case study using hydrodynamic and water quality modeling in the Nile River, Egypt - Amal Magdy; Elsayed Ramadan; Ahmed Moussa; Abdelazim Negm (Marine Pollution Bulletin, 2026)

Recent strategies and methodological advances for microbial natural product research in the post-genomics era - Abdelrahman M. Sedeek; Mariam Hassan; Tarek R. Elsayed; Mohamed A. Ramadan (Archives of Microbiology, 2026)

Protamine sulphate for heparin reversal in percutaneous cardiac interventions: a systematic review and meta-analysis of randomized controlled trials - Elsayed Balbaa; Ahmed Farid Gadelmawla; Abdelrahman M. Tawfik; Ahmed Naeem; Ahmed Elbataa; Mohammad Bazzazeh; Ahmed Ramadan Fatiem; Khaled Ali; Obieda Altobaishat; Mohamed Abuelazm (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Vascular complications after percutaneous cardiac interventions are a significant cause of morbidity that affects post-procedural prognosis. Data about the efficacy and safety of routine protamine sulphate to prevent these complications remain scarce. Hence, we aim to assess the efficacy and safety of routine protamine sulphate use for heparin reversal in patients undergoing percutaneous cardiac interventions. We systematically searched PubMed, Embase, Cochrane, Scopus, and Web of Science for randomized controlled trials (RCTs) until September 2024. The RCTs’ quality was assessed using the Cochrane tool (RoB 2). Using R, we pooled dichotomous outcomes using risk ratios (RR) and continuous outcomes using mean differences (MD), both along the corresponding 95% Confidence interval (CI). PROSPERO ID: (CRD42024593002). Six RCTs with 1,076 patients were eligible. Hemostasis success was significantly higher in the protamine group (RR, 1.06; 95% CI [1.01–1.10]; P = 0.01), and the length of hospital stay was significantly shorter (MD, -0.46; 95% CI [-0.65, -0.26]; P < 0.01). There was no significant difference between both groups in stroke (RR, 0.60; 95% CI [0.18–2.03]; P = 0.41), major bleeding ( P = 0.25), minor bleeding ( P = 0.11), life-threatening bleeding ( P = 0.65), time to ambulation ( P = 0.13), all-cause mortality ( P = 0.92), hematoma/pseudoaneurysm ( P = 0.92), and major vascular complications ( P = 0.70). While protamine improved hemostasis success, its effect on reducing bleeding events and time to ambulation was insignificant. Also, reducing the length of hospital stay in the protamine group highlights its potential clinical benefit. Graphical Abstract

Reprogramming the hepatic immune microenvironment with mirtazapine in early neoplastic transformation: Evidence from a diethylnitrosamine-induced rat model - Elsayed A. Elmorsy; Sameh Saber; Ahmad H. Alhowail; Abousree T. Ellethy; Enas A. Mohamed; Hamad Alsaykhan; Hatim Y. Alharbi; Omar Almansour; Abdelrahman El-Sayed; Manal Mohamed Hatem; Ahmed Kaid Alantry; Walaa A. Allam; et al. (Chemico-Biological Interactions, 2025)

Efficacy and safety of colchicine post myocardial infarction: a systematic review, meta-analysis and meta-regression analysis of randomized clinical trials - Farhan Naeem; Shehroze Tabassum; Muhammad Burhan; Elsayed Balbaa; Ahmed Ibrahim; Shrouk Ramadan; Usama Qamar; Fatima Saeed; Mohamed Abuelazm; Dmitry Abramov; Timir K. Paul; Yasar Sattar (European Journal of Clinical Pharmacology, 2025)

Alogliptin attenuates testicular damage induced by monosodium glutamate in both juvenile and adult male rats by activating autophagy: ROS dependent AMPK/mTOR - Manal Mohammad Morsy; Heba A. Hassan; Reham M. Morsi; Ola Elsayed Nafea; Azza I. Farag; Rania Saad Ramadan (Reproductive Toxicology, 2025)

Omega-3 supplementation in migraine prophylaxis: An updated systematic review and meta-analysis - Haneen Sabet; Abdallah Abbas; Ibraheem M alkhawaldeh; Shrouk Ramadan; Moaz Elsayed Abouelmagd; Ebrahem Salah Abdul-Hamid; Ahmed Elbataa; Mona Mahmoud Elsakka; Anas Mansour; Mostafa Hossam El Din Moawad; Aynur Ozge (PharmaNutrition, 2025)

Integration of hydrodynamic and water quality modeling to mitigate the effects of spill pollution into the Nile River, Egypt - Elsayed M. Ramadan; Ahmed Moussa; Amal Magdy; Abdelazim Negm (Environmental Science and Pollution Research, 2024)

Use of remote sensing, spatial and geophysical modeling, and real recharging capabilities to identify suitable areas for groundwater exploitation in dry coastal areas - Hossam H. Elewa; Ahmed M. Nosair; Amin Ibrahim; Martina Zelenakova; Katarzyna Pietrucha-Urbanik; Hazem M. Habib; Nermeen A. Abdel Moneam; Rania M. Ragab; Elsayed M. Ramadan (Journal of Environmental Management, 2024)

Potential inhibitory effect of geraniol isolated from lemongrass ( Cymbopogon commutatus Stapf) on tilmicosin-induced oxidative stress in cardiac tissue - Rebai Ben Ammar; Sarah Abdulaziz Alamer; Maged Elsayed Mohamed; Duaa Althumairy; Saeed Y. Al-Ramadan; Manal Alfwuaires; Nancy S. Younis; Thnaian A. Althnaian; Ibrahim R. I. H.; Peramaiyan Rajendran (Natural Product Research, 2024)

Metabolic profiling and cytotoxic activities of ethanol extract of Dypsis leptocheilos aerial parts and its green synthesized silver nanoparticles supported by network pharmacology analysis - Marwa Hassan Hussaen Mohammed; Ashraf Nageeb Elsayed Hamed; Sammar Fathy Elhabal; Fatma A. Mokhtar; Usama Ramadan Abdelmohsen; Mostafa Ahmed Fouad; Mohamed Salah Kamel (South African Journal of Botany, 2023)

Chemical composition and anti-proliferative activities of Hyophorbe lagenicaulis aerial parts and their biogenic nanoparticles supported by network pharmacology study - Marwa Hassan Hussaen Mohammed; Ashraf Nageeb Elsayed Hamed; Sammar Fathy Elhabal; Fatma A. Mokhtar; Usama Ramadan Abdelmohsen; Mostafa Ahmed Fouad; Mohamed Salah Kamel (South African Journal of Botany, 2023)

Impact of Modern Irrigation Methods on Groundwater Storage and Land Subsidence in High-water Stress Regions - Ismail Abd-Elaty; Ismail Fathy; Alban Kuriqi; Am Pris John; Salvatore Straface; Elsayed M. Ramadan (Water Resources Management, 2023)
Water resources management in high-stress regions is a large-scale problem affecting food and water security. Therefore, modern irrigation systems such as sprinklers, subsurface, and drip irrigations are applied to manage the water shortage in regions of the Nile delta. Because of the increase in population rate and climate change, freshwater supplies are significantly limited and must be efficiently managed. Consequently, Egypt plans to implement MIS in the old land of the Nile delta. The current study aims to investigate and model the recharge from the excess irrigation system that affects groundwater storage and land subsidence unexpectedly. The visual modflow was applied to investigate the groundwater heads and drawdown. At the same time, the analytical solution based on Terzaghi theory, and the surfer software was used to estimate and map the land subsidence. For this reason, we investigated the groundwater drawdown in the high-water shortage of Egypt’s Nile delta. Three scenarios were considered by changing irrigation methods and their Impact on land subsidence in the Nile Delta Aquifer (NDA). Therefore, the results of this study demonstrated that the groundwater drawdown reached 2.60 m, 4.20 m, and 6.50 m, respectively. In contrast, the land subsidence outstretched 26 m, 44 m, and 65 cm for the sprinkle sub-surface. Future design infrastructures such as pipelines, roads, irrigation networks, canals, and water structures should consider land subsidence due to modern irrigation systems (MIS).

LC-MS-based identification of bioactive compounds and hepatoprotective and nephroprotective activities of Bignonia binata leaves against carbon tetrachloride-induced injury in rats - Mamdouh Nabil Samy; Ashraf Nageeb Elsayed Hamed; Basma Khalaf Mahmoud; Eman Zekry Attia; Usama Ramadan Abdelmohsen; Michael Atef Fawzy; Mina Ezzat Attya; Mohamed Salah Kamel (Natural Product Research, 2022)

Metabolomic profiling and biological investigation of Tabebuia Aurea (Silva Manso) leaves, family Bignoniaceae - Basma Khalaf Mahmoud; Ashraf Nageeb Elsayed Hamed; Mamdouh Nabil Samy; Usama Ramadan Abdelmohsen; Eman Zekry Attia; Michael Atef Fawzy; Rana Hosny Refaey; Mohammad Alaraby Salem; Sheila Marie Pimentel-Elardo; Justin R. Nodwell; Samar Yehia Desoukey; Mohamed Salah Kamel (Natural Product Research, 2021)

Whole-genome sequencing of Egyptian multidrug-resistant Klebsiella pneumoniae isolates: a multi-center pilot study - May Sherif; Mattia Palmieri; Caroline Mirande; Hadir El-Mahallawy; Hebatallah G. Rashed; Fadwa Abd-El-Reheem; Arwa Ramadan El-Manakhly; Radwa Ahmad Rabea Abdel-latif; Aliaa Gamaleldin Aboulela; Laila Yosef Saeed; Soheir Abdel-Rahman; Eman Elsayed; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Two-stage cultivation of Chlorella vulgaris using light and salt stress conditions for simultaneous production of lipid, carotenoids, and antioxidants - Hamdy Elsayed Ahmed Ali; Eman A. El-fayoumy; Wessam E. Rasmy; Ramadan M. Soliman; Mohd Azmuddin Abdullah (Journal of Applied Phycology, 2021)

Response Surface Methodology as a Useful Tool for Development and Optimization of Sustained Release Ketorolac Tromethamine Niosomal Organogels - Mahmoud M. A. Elsayed; Saleh Abd El Rasoul; Abd El hakim Ramadan; Amal K. Hussein (Journal of Pharmaceutical Innovation, 2020)

Using geographic information system (GIS) modeling in evaluation of canals water quality in Sharkia Governorate, East Nile Delta, Egypt - Elsayed M. Ramadan; Maha R. Fahmy; Ahmed M. M. Nosair; Abir M. Badr (Modeling Earth Systems and Environment, 2019)

The changing patterns of bladder cancer in Egypt over the past 26 years - Ashley S. Felix; Amr S. Soliman; Hussein Khaled; Mohamed S. Zaghloul; Mousumi Banerjee; Manal El-Baradie; Mohamed El-Kalawy; Alaa A. Abd-Elsayed; Kadry Ismail; Ahmed Hablas; Ibrahim A. Seifeldin; Mohamed Ramadan; et al. (Cancer Causes & Control, 2008)